Immunization Status With Children Nutrition Status In The Working Area Of Puskesmas Kedamean, Gresik - Nada, Zanuba Q; Andriani, Dini; Prabantoro, Benedictus TR (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Immunization in the national health system is one form of health protection that is very effective in preventing infant and under-five mortality rates. Children who are notimmunized do not have immunity against the disease, so they will fall ill, possibly causing adecline in nutritional status. Infectious diseases and immune functions are interconnected and will ultimately affect the nutritional status in children. Purpose: To determine the correlation between immunization status and nutritional status of children under five in the Health Center Community or Pusat Kesehatan Masyarakat in Indonesian (Puskesmas) in Gresik Regency, East Java. Method: This study used an observational analytic research method with a cross-sectional research design. The samples of this research are toddlers aged 1-5 years old and mothers who have MCH books. The study was conducted by collecting data using a questionnaire to be filled out by mothers of children under five. Then, the researchers collected data by recording the immunization status of children under five by looking at the MCH book. Then, we measured the body weight and height of the toddler. Results: Based on the results of statistical calculations using the chi-square test regarding the analysis of the relationship between immunization status and nutritional status of children under five obtained a significance value of p = 0.220: pâ‰¥0.05 (value Î±). Conclusion: There was no significant relationship between immunization status and nutritional status of children under five years old in the Puskesmas Kedamean in GresikRegency